English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

1.) Solve for X.
3 ^3-5x = 24

2.) Solve for X.
3 ln (-2x + 4) = -3

2006-12-04 11:57:22 · 5 answers · asked by savj14 2 in Science & Mathematics Mathematics

In number one, 3 is actually raised to the 3-5x power. Instead of 3 raised to the 3rd power minus 5.

So the equation would look like this.

3^(3-5x) = 24

Sorry for the typo

2006-12-04 12:18:08 · update #1

5 answers

Ok, number 2:

--->Ln (-2x+4) = -3/3

--->e^Ln(-2x+4) = e^-1(you have to use the number e (2.718281...) to find X, this process eliminates Ln):


---> -2x+4=e^-1

--->-2x=(e^-1)-4

---> x = ((e^-1)-4)/-2 (I hope u understand)

Answer: x= 1.81606

2006-12-04 12:16:21 · answer #1 · answered by Mila S 4 · 0 0

1.) Solve for X.
3³-5x = 24
-5x = 24 -27
x = -3/-5
x = 0,6

2.) Solve for X.
3 ln (-2x + 4) = -3
-6x + 12 = -3
-6x = -3 -12
-6x = -15
x = 15/6 = 5/2 = 2,5

2006-12-04 20:06:32 · answer #2 · answered by aeiou 7 · 0 0

3 ^3-5x = 24
27 - 5x = 24
27 - 24 = 5x
3 = 5x
3/5 =x

3 ln (-2x + 4) = -3
ln (-2x + 4) = -1
e^(-2x + 4) = e^-1
-2x+4 = 1/e
-2x = 1/e -4
x = - (1/e -4)/2 = - (1-4e)/(2e) = (4e-1)/(2e)

2006-12-04 20:13:50 · answer #3 · answered by ironduke8159 7 · 0 0

1)
3^3 - 5x = 24
27 - 5x = 24
5x = 27-24
5x = 3

x=3/5

2) ?

2006-12-04 19:59:28 · answer #4 · answered by Xiangwei Xi 3 · 0 0

2) 3ln(-2x+4)=-3 => -2x+4=e^(-1) => x = (e^(-1)-4)/(-2)

2006-12-04 20:01:38 · answer #5 · answered by Petterjunni 1 · 0 0

fedest.com, questions and answers